Utilization of Corn Waste for Goat Feed in Proko Hall, Brangkal Village, Bandarkedungmulyo District, Jombang Regency - Burhanuddin, Imam; Aini, Nurul; Puspaningrum, Yessita (AGARICUS: Advances Agriculture Science & Farming, 2025)
Corn, a leading commodity with potential for development in Proko Hamlet, contains agricultural waste that can be used as animal feed. Currently, corn harvest waste is only used as fuel or even disposed of carelessly, leading to environmental pollution. The availability of quality feed ingredients is one of the problems encountered by partners. Therefore, corn cobs, leaves, and husks are used as additives in fermented animal feed. The purpose of this study was to analyze the impact and benefits of corn waste used as raw material for goat feed. The method used consisted of three stages: observation surveys, interviews, and training on corn waste processing. The results of this study indicate that corn waste can be processed into raw material for animal feed and organic fertilizer. This processing has the potential to reduce environmental pollution caused by agricultural waste. In addition, utilizing this waste can also increase agricultural productivity. Furthermore, this activity also encourages increased awareness and participation of the community, particularly farmer groups in Proko Hamlet, in sustainable waste management. Based on the results of interviews with several respondents, it was discovered that processing corn waste as raw material for animal feed has the potential to be an alternative to quality fermented feed. In addition, this approach is considered sustainable and environmentally friendly, thus supporting efforts to manage agricultural waste more efficiently and responsibly